Human laryngeal sensory receptor mapping illuminates the mechanisms of laryngeal adductor reflex control. (8th September 2018) - Sinclair, Catherine F.; Téllez, Maria J.; Ulkatan, Sedat
Abstract : Objective: The laryngeal adductor reflex (LAR) is an airway protective response triggered by sensory laryngeal receptors. It is unknown whether different glottic and supraglottic subsites vary in their reflex elicitation abilities. The recent discovery that a bilateral LAR is present in humans under general anesthesia upon laryngeal mucosal stimulation has enabled us to map the sensory receptor density for LAR elicitation at different laryngeal subsites. Our findings expose the likely mechanisms of LAR control. Methods: Prospective series of 10 patients undergoing laryngoscopy. Laryngeal subsites (epiglottic tip, membranous vocal fold, midventricular vocal fold, posterior supraglottis, epiglottic petiole) were stimulated via direct laryngoscopy with a bipolar probe. Vocal fold responses were recorded by endotracheal tube and hook wire electrodes, and visual observation. Results: Posterior supraglottic stimulation elicited bilateral LARs in all patients at all intensities. Membranous vocal folds, epiglottic petiole, and subglottis elicited no LAR. Ventricular fold and epiglottic tip responses converted from ipsi‐ to bilateral at high intensities. Conclusion: There are likely three checkpoints for control of the LAR in humans. These checkpoints protect against inappropriate LAR activation during volitional tasks without compromising airway protection: 1) topographical differences in receptor density with the highest density in subsites most likely to contact foreign substances; 2) absence of receptors in membranous vocal folds; and 3) central summation threshold for crossed interneuron activation at brainstem level where only strong intensity stimuli will elicit bilateral responses. Checkpoint dysfunction provides a novel framework to diagnose and treat disease processes, including aspiration, laryngospasm, and sudden infant death. Level of Evidence: 4. Laryngoscope, E365–E370, 2018